2011
DOI: 10.3762/bjoc.7.140
|View full text |Cite
|
Sign up to set email alerts
|

NMR studies of anion-induced conformational changes in diindolylureas and diindolylthioureas

Abstract: SummaryThe conformational properties of 1,3-diindolylureas and thioureas were studied by a combination of heteronuclear NMR spectroscopy and quantum mechanics calculations. NOE experiments showed that the anti–anti conformer along the C7–N7α bonds was predominant in DMSO-d 6 solution in the absence of anions. Anion-induced changes in the 1H and 15N chemical shifts confirm the weak binding of chloride anions with negligible conformational changes. Strong deshielding of ureido protons and moderate deshielding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…A similar hydrogen‐bond interaction has been observed in reference 18 for the acetate and benzoate anions, where it was demonstrated that receptor 30 has three possible conformations (i.e., syn – syn , syn – anti and anti – anti ). In the absence of anion, the receptor is in the anti – anti conformation and in the presence of an anionic guest the complex adopts the syn – syn conformation.…”
Section: Resultssupporting
confidence: 82%
“…A similar hydrogen‐bond interaction has been observed in reference 18 for the acetate and benzoate anions, where it was demonstrated that receptor 30 has three possible conformations (i.e., syn – syn , syn – anti and anti – anti ). In the absence of anion, the receptor is in the anti – anti conformation and in the presence of an anionic guest the complex adopts the syn – syn conformation.…”
Section: Resultssupporting
confidence: 82%
“…Because changes of 1 H NMR chemical shifts upon complexation of urea, thiourea, DIU , and DIT (but not sulfamide) with anions have been observed, NMR chemical shift calculations were performed for the free and complexed DIS (Table ). As expected, the chemical shifts for H 1 and H 8α/β were the most affected by the presence of an anion, with increased values relative to TMS when compared with the anion‐free DIS , in either the gas phase or implicit DMSO.…”
Section: Resultsmentioning
confidence: 99%
“…Some promising examples are diindolylureas ( DIU ) and diindolylthioureas ( DIT ), which have 4 N–H groups and high affinity to halides and oxoanions . These anions participate in the molecular recognition of DIU and DIT , inducing the conformational shift in DMSO solution towards a high‐energy conformation in an anion‐free environment …”
Section: Introductionmentioning
confidence: 99%
“…Table provides a summary of the diagnostic 1 H NMR, 13 C NMR, and 15 N NMR chemical shifts, whereas the complete NMR data is reported in the Experimental Section. The 1 H NMR and 1 H, 15 N HSQC spectra of 1 – 4 are provided in Figures S5–S8 and S9–S12, respectively . The 1 H, 15 N HMBC spectrum of 4 is also included (Figure S13).…”
Section: Resultsmentioning
confidence: 99%